2004
DOI: 10.1080/00140130310001629757
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive strategy changes as a function of task demands: a study of car drivers

Abstract: When drivers perform additional tasks while driving, research shows conflicting results: primary driving performance may deteriorate but adaptive changes such as reducing driving speed have also been noted. We hypothesized that the nature of the secondary task may be important: drivers may give more priority to tasks that serve goals of the driving task itself, for example route finding, than tasks not directly relevant for driving, for example tuning the radio. The main objective of the present driving simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 24 publications
5
35
0
3
Order By: Relevance
“…With increasing levels of dangerous driving convictions, this line needs to be clearer to drivers (Cnossen et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing levels of dangerous driving convictions, this line needs to be clearer to drivers (Cnossen et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the driver is, ultimately, to reach the destination safely (Cnossen et al, 2004), with behaviour regulated to achieve this goal (Groeger, 2000). Technology has expanded the potential goals available to drivers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, participants seemed to place a higher priority on the stop/go task since the brake first strategy occurred more often than the pedestrian first strategy. Participants may have preferred the brake first strategy to protect driving performance from the pedestrian task, which was not in direct service of the driving task (e.g., Cnossen, Meijman, & Rothengatter, 2004). High priority distractions that directly serve the driving task (e.g., destination entry) may be more likely to cause central processing bottlenecks and interfere with driving compared to distractions of lower priority.…”
Section: Discussionmentioning
confidence: 99%
“…Cnossen, Meijman and Rothengatter [30] reported that drivers were highly motivated to get route information while driving to the detriment of their driving performance in high demand driving situations. Resumability implies that a driver may string a task out over some long period of time which is unrepresentative of typically motivated human behaviour.…”
Section: Resumability (Interruptibility)mentioning
confidence: 99%